Modos de objetivação do sujeito Charles Manson: um estudo arqueogenealógico - SILVA, Paulo Círio (2023)
Charles Manson was a fake American guru who frightened the United States in the summer of 1969 by having planned to murder the American actress Sharon Tate – and her friends – and the couple LaBianca. In 1967, he organized in an abandoned ranch the famous cult Manson Family, whose group of followers worshiped him as if he was a sort of spiritual counselor, a messiah. This way, the present dissertation aims to analyze how is made the objectification of the subject Charles Manson by the American media through statement of his former followers and the biographical novel written by Jeff Guinn in 2014. The theoretical contribution for this survey is A Arqueologia do Saber (FOUCAULT, 2008); Dicionário de Teologia Fundamental (BARAÚNA, 1994); and O Governo de Si e dos Outros (FOUCAULT, 2010). In view of, the methodology worked to development of corpus is bibliographical and analyzes the objectification of subject from the American media through statement of Manson former followers and biography written by Guinn. The discursive formation presented by biographer Jeff Guinn – biographer, historian, political scientist – reveals a regularity. Charles Manson is objectified as a manipulator, seductive, groomer, violent, cruel, as well as a victim in a problematic familiar relationship in various moments which he was abandoned resulting in the formation of a problematic and transgressive character. For his followers, whose speech was said on media, Manson is objected as a protector, a shepherd. It is important to be highlighted his strategies of power were seduction and grooming. The behavior as a shepherd was a technique of manipulation developed by Manson who did not matter in protecting because he wanted his members were submissive in the Family. In the view of media, the subject is objected like a insane, a cruel man who pretended to care his followers to obtain money and other advantadge. In this process of objectivation about subject, the interviews describe Manson as a lovely leader and at the same time a frightening man.